28-Day Oral Chronic Toxicity Study of Arctigenin in Rats - Yu-jun Tan; Yu-jun Tan; Yu-shan Ren; Yu-shan Ren; Lei Gao; Lei Gao; Lan-fang Li; Lan-fang Li; Li-juan Cui; Li-juan Cui; Bin Li; Bin Li; et al. (Frontiers Media S.A., 2018)
Arctium lappa (burdock) is the most popular daily edible vegetable in China and Japan because of its general health tonic effects. Previous studies focused on the beneficial role of Arctigenin but neglected its potential side-effects and toxicities. In the present study, the sub-chronic toxicity profile of Arctigenin following 28 days of consecutive exposure was investigated in rats. The results showed that during the drug exposure period, Arctigenin-12 mg/kg administration resulted in focal necrosis and lymphocytes infiltration of heart ventricular septal muscle cells. In the kidney cortical zone, the renal tubular epithelial cells were swollen, mineralized, and lymphocyte infiltrated. In the liver, the partial hepatocyte cytoplasm showed vacuolation and fatty changes, focal necrosis, and interstitial lymphocyte infiltration. In the rats that underwent 36 mg/kg/day administration, there was bilateral testis and epididymis atrophy. In the lung and primary bronchus, erythrocytes and edema fluid were observed. Changes of proestrus or estrus were observed in the uterus, cervix, and vagina intimal epithelial cells. Lymphocytic focal infiltration occurred in the prostate mesenchyme. The high dosage of Arctigenin only decreased the body weight at day 4. At the end of the recovery period, histopathological changes were irreversible, even after withdrawal of the drug for 28 days. Focal necrosis still existed in the heart ventricular septal muscle cells and hepatocytes. Lymphocyte infiltrations were observed in the heart, renal cortex, hepatocyte, and pancreas exocrine gland. Meanwhile, atrophy occurred in the testicles and pancreas. In addition, in the Arctigenin-12 mg/kg group, creatinine (CREA) and brain weight were both significantly increased. The toxicokinetical study demonstrated that Arctigenin accumulated in the organs of rats. The food consumption, hematological, and biochemical parameters were not associated with the above results. These contradictory results might result from the lesions induced by Arctigenin, which were not sufficiently serious to change the parameters. These results suggest that Arctium lappa should be consumed daily with caution because of the potential toxicity induced by Arctigenin. According to all results, the lowest observed adverse effect level (LOAEL) was induced by 12 mg/kg daily exposure to Arctigenin, and the No-observed-adverse-effect-level (NOAEL) should be lower than 12 mg/kg.